1994
DOI: 10.1242/jeb.191.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Excretion in Freshwater Rainbow Trout (Oncorhynchus Mykiss) and the Importance of Gill Boundary Layer Acidification: Lack of Evidence for Na+/NH4+ Exchange

Abstract: Net ammonia fluxes (JAmm) were measured in adult freshwater rainbow trout in vivo under a variety of conditions designed to inhibit unidirectional sodium uptake (JinNa; low external [NaCl], 10(-4) mol l-1 amiloride), alter transbranchial PNH3 and NH4+ gradients [24 h continuous (NH4)2SO4 infusion, or exposure to 1 mmol l-1 external total ammonia at pH 8] and prevent gill boundary layer acidification (5 mmol l-1 Hepes buffer). Inhibition of JinNa with amiloride or low external [NaCl] under normal conditions red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…3(a)]. This increase is consistent with other studies (Wilkie & Wood, 1991;Wilson et al, 1994;McGeer & Eddy, 1998), but the data do not agree with the study by Yesaki & Iwama (1992), where it was shown that hard water had a protective effect on ammonia accumulation in the plasma. Liver ammonia also did not change in any condition during the exposure [Fig.…”
Section: Discussionsupporting
confidence: 63%
“…3(a)]. This increase is consistent with other studies (Wilkie & Wood, 1991;Wilson et al, 1994;McGeer & Eddy, 1998), but the data do not agree with the study by Yesaki & Iwama (1992), where it was shown that hard water had a protective effect on ammonia accumulation in the plasma. Liver ammonia also did not change in any condition during the exposure [Fig.…”
Section: Discussionsupporting
confidence: 63%
“…8). Indeed, this was larger than the marginal decreases in ammonia efflux (0-30%) normally seen in freshwater teleosts in response to amiloride blockade of Jin Na (Kirschner et al, 1973;Wright and Wood, 1985;Wilson et al, 1994;Nelson et al, 1997;Clarke and Potts, 1998;Patrick and Wood, 1999). While originally seen as evidence for Na + /NH4 + exchange, the latter observations have more recently been interpreted as an inhibition of 'diffusion trapping' of NH3 in gill boundary layer water associated with blockade of H + extrusion via Na + /H + and/or Na + channel/H + -ATPase systems (Wilson, 1996;Wilkie, 1997).…”
Section: Nitrogen Metabolism and Ammonia Excretionmentioning
confidence: 72%
“…In this regard, the stingray is similar to most freshwater teleosts, in which a 60-95% blockade of Na + uptake induced by this concentration of amiloride has been widely reported (e.g. Kirschner et al, 1973;Wright and Wood, 1985;Wilson et al, 1994;Nelson et al, 1997;Clarke and Potts, 1998;Patrick and Wood, 1999). Interestingly, in two native Rio Negro characids that demonstrated the high-capacity, high-affinity, low-pHresistant-strategy of Na + transport (i.e.…”
Section: Mechanisms Of Ca 2+ Transport and Bindingmentioning
confidence: 79%
“…Exposure to HEA in live intact fish (1 mmol l −1 NH 4 + for 24 h) resulted in a 4.5‐fold increase in plasma ammonia, reaching an average concentration of 1199 ± 144 μmol l −1 (Figure 2a), similar to the response observed in other studies on adult trout (Liew et al ., 2013; Nawata et al ., 2007; Sinha et al ., 2013; Wilson et al ., 1994; Wood & Nawata, 2011). Skin tissue ammonia concentration in these same fish increased from 2322 ± 302 μmol kg −1 in control fish to 4018 ± 402 μmol kg −1 following HEA exposure (Figure 2b), demonstrating for the first time that ammonia accumulates in the skin in response to HEA.…”
Section: Figurementioning
confidence: 99%
“…A role for the skin in whole-body ammonia excretion is also supported by increased transcript abundance of genes encoding ammonia-transporting Rhesus (Rh) glycoproteins in this tissue in response to manipulations of ammonia status, such as high environmental ammonia (HEA; Hung et al, 2007;Nawata & Wood, 2009;Nawata et al, 2007). HEA exposure initially results in significant ammonia uptake and elevated plasma ammonia, followed by the re-establishment of outwardly directed ammonia excretion (Nawata et al, 2007;Wilson et al, 1994;Wood & Nawata, 2011;Zimmer et al, 2010). This occurs in conjunction with increased expression of Rh genes in the gills (Hung et al, 2007;Nawata et al, 2007Nawata et al, , 2010Sinha et al, 2013;Zimmer et al, 2010Zimmer et al, , 2017.…”
mentioning
confidence: 99%